Skin manifestations in VEXAS syndrome: specific clonal infiltrates vs non-specific reactive findings - Utz, Samuel; Lehmann, Mathias; Seyed Jafari, Morteza; Bonadies, Nicolas; Lötscher, Fabian; Maurer, Britta; Seitz, Luca; Vassella, Erik; Wolf, Ronald; Borradori, Luca; Feldmeyer, Laurence (Case reports in dermatology, 2025)
Introduction: VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) is a myeloid-driven, adult-onset inflammatory syndrome associated with hematological neoplasms and a wide range of manifestations, including fever, pancytopenia, vasculitis, polyarthritis, and pulmonary infiltrates. Skin lesions are present in up to 90% of cases, but remain heterogeneously defined. We present three patients with VEXAS syndrome and cutaneous manifestations admitted to a tertiary referral hospital. Case Presentations: The three male patients with a median age of 66 years, showed chronic mucocutaneous xanthomatous lesions, a persistent neutrophilic dermatosis en plaques as well as eczematous lesions, respectively. Histology showed either a dermal neutrophilic infiltrate, leukocytoclasia without vasculitis with abundant interstitial foamy CD68-positive macrophages, superficial and deep neutrophilic dermatitis and panniculitis, or a spongiotic dermatitis. Somatic mutations in UBA1 were detected in all 3 patients, but two also had the same UBA1 mutation in the skin. Conclusion: VEXAS syndrome is associated with several cutaneous manifestations, the features of which may be atypical and pose a diagnostic and classification challenge. Histology often shows neutrophilic dermatosis with leukocytoclasia without frank leukocytoclastic vasculitis, and an occasional accumulation of foamy macrophages in the superficial and deep dermis. The cutaneous lesions likely reflect either the activation of autoinflammatory pathways or the presence of myelodysplastic cells in the skin. They may represent either “non-specific” reactive findings or “specific” cutaneous manifestations associated with a clonal infiltration of abnormal myeloid cells.